Aplicação de wavelets em inpainting digital - Ignácio, Ubiratã Azevedo (Universidade do Vale do Rio do Sinos, 2007)
Digital Inpainting is a recent techinique that allows the filling of missing information in images. One important attribute of a digital inpainting technique is the ability of altering an image in such a way that it is not simple for the human observer to detect the modification, characterizing an undetectable modification. The strategies for filling missing parts vary since the first inpainting model, but one thing that remains is the fact that the filled area must be coherent with the original part of the image. Current techniques handle the filling as a structure propagation problem, working directly in the image color domain, and based on concepts like Total Variation or Partial Diferential Equations. In this work, we present a digital inpainting model that works exclusively in Wavelet domain,filling the target area with a texture synthesis mechanism using the properties of the Wavelet Transform
Wavelet transform in digital inpainting
Keywords: inpainting digital; processamento digital; transformada; wavelet; imagem; digital inpainting; image completion; image restoration; texture filtering; texture sintesis; wavelet transform; image processing; Ciências Exatas e da Terra